The Stromal Derived Factor-1 (SDF-1) Secretion Attracts Stem Cells and Accelerates the Skin Wound Healing Against the Background of Its Closure With Dermal Fibroblasts Associated With Polylactide Film - Baranovskiy, Alexey; Shapovalova, Yelena; Kuzminov, Boris; Baranovskiy, Yuri; Lugin , Igor; Kutuzova , Lilian; Pyatigorskaya , Nathalia; Rostovskaya , Vera; Yuferov , Daniil; Kabanov , Denis; Demyashkin, Grigory (Scripta Medica, 2025)
Background/Aim. Chronic skin wounds are a huge clinical problem, leading to the need for prolonged treatment and significant health care expenses. Regenerative engineering using tissue technologies and cellular constructs offers promising alternatives for treatment. The aim of this research was to evaluate the levels of stromal-derived factor-1 (SDF-1) expression and the presence of CD34+ mesenchymal stem cells (MSC) in regenerating skin wounds treated with polylactide films combined with dermal allofibroblasts. Methods. Forty-seven white mature male mice line C57/B1 were allocated into two groups – control and experimental. In the experimental group, a standard skin wound was created and treated with polylactide films with allofibroblasts. Biopsies were taken at various time points for histological and immunohistochemical analysis of SDF-1 and CD34 expressions. Cellular indices were determined by counting positive cells per 100 cells under a microscope. Statistical analysis was performed using nonparametric tests. Results. SDF-1 expression peaked on day 7 and then declined, disappearing by day 15, while the number of MSCs followed a similar trend. Delayed and prolonged SDF-1 expression and the presence of MSCs were observed in control wounds. Enhanced epithelialisation and granulation tissue formation were observed in the experimental group, indicating accelerated wound healing. Conclusion. Transplantation of polylactide films with dermal allofibroblasts promotes early and active secretion of SDF-1, which promotes MSC recruitment and accelerates skin wound regeneration.